PERILAKU KONSUMEN DALAM PROSES PEMBELIAN IKAN HIAS AIR LAUT DI BANDA ACEH AKUARIUM KOTA BANDA ACEH - Nabila Ukhty (Jurnal Bisnis Dan Kajian Strategi Manajemen, 2017)
AbstractCompetition ornamental fish in Banda Aceh increasingly stringent, requiring appropriatemarketing strategies to excel compete. One way that can be taken by employers ornamental fishincluding Banda Aceh Aquarium, is a strategy to increase sales volume by studying and knowing thefactors that influence consumers decide to buy ornamental fish. The purpose of this study was todetermine (1) the consumer characteristics of ornamental fish in Banda Aceh Aquarium, (2)ornamental fish type whatever demand by consumers, and (3) factors that influence the purchaseof ornamental fish in Banda Aceh Aquarium.The method used in this study is a survey method.The data will be used in this study are primary and secondary data. The sampling technique usedwas purposive sampling method, with a total sample of 100 respondents. Analysis of the data : (1)descriptive analysis to get an overview of consumer characteristics and type of ornamental fish thatconsumers demand; (2) factor analysis with factor analysis PCA extraction method. The resultsshowed that the majority of respondents were male (71%), aged 20-30 years (81%), unmarried(73%), family size 3-5 people, educated scholars (49%), private sector employees ( 42%), andthe average monthly income of more than Rp. 2,500,000. Ornamental fish species are widelypurchased by consumers in the top five is Clown Fish, Blue Stone, Rivet, Beauty and Six Letter /Dori. The factors that influence consumer decisions in the purchase of ornamental fish are culturalfactors, social factors, personal factors, and psychological factors.Keywords: consumer behavior, Banda Aceh aquarium, ornamental fish